STRATEGI MARKETING MIX PRODUK MAKANAN KOREA DALAM MENINGKATKAN KEPUASAN KONSUMEN PADA HOME INDUSTRY UNNIEFOOD TULUNGAGUNG - Yuniar Dwi Pangestu; Siswahyudianto Siswahyudianto (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2022)
The influence of globalization creates changes in people's lifestyles, especially young people. One of the influences of globalization is that the lifestyle in choosing foods that are in demand is more inclined towards Korean style. The Korean Wave or Hallyu Wave is one of the impacts of the globalization of food style changes from traditional to modern in Indonesia. The explosion of Korean trends in Indonesia has made culinary business actors go with this flow. This is the reason why the Unniefood Home industry is one of the home businesses that sells a variety of Korean foods that have a spicy taste. The increasingly fierce competition makes this business have a strategy that is carried out for consumer satisfaction, namely using a marketing mix and a consumer satisfaction strategy.  The purpose of this study is to determine the application of the marketing mix strategy and the application of the consumer satisfaction strategy in the home industry of Unniefood Tulungagung. The research method used in this study is a type of field research with a qualitative approach using descriptive methods. Data collection techniques use observation, interview, and documentation methods. The results of this study show that the application of the marketing mix strategy with the 11p indicator has been implemented properly and correctly. There are only two indicators that are not well implemented, namely place and physical evidence, which still makes Consumers and Unniefood resellers feel disappointed. The implementation of the consumer satisfaction strategy has been implemented properly and correctly to make consumers and resellers feel satisfied